2002
DOI: 10.1113/jphysiol.2001.013225
|View full text |Cite
|
Sign up to set email alerts
|

Differential ontogeny of GABABreceptor‐mediated pre‐ and postsynaptic modulation of GABA and glycine transmission in respiratory rhythm‐generating network in mouse

Abstract: Rhythm generation in mature respiratory networks is influenced strongly by synaptic inhibition. In early neonates, GABAA‐receptor‐ and glycine‐receptor‐mediated inhibition is not present, thus the question arises as to whether GABAB‐receptor‐mediated inhibition plays an important role. Using brainstem slices of neonatal mice (postnatal day, P0‐P15), we analysed the role of GABAB‐mediated modulation of GABA and glycine synaptic transmission in the respiratory network. Blockade of GABA uptake by nipecotic acid (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
52
0
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(56 citation statements)
references
References 42 publications
2
52
0
2
Order By: Relevance
“…Since catecholaminergic neurons in this region receive serotonergic synaptic input (Pickel et al, 1984), it is possible that the effects we have observed in 5HT neuron-deficient Pet-1 −/− mice are indirect and result from the loss of 5HT modulation of noradrenergic influences on central rhythm generation. In addition, a developmental switch from excitatory to inhibitory γ-aminobutyric acid (GABA)-mediated neurotransmission has been shown to occur in mouse preBötC neurons during the first postnatal week (Ritter and Zhang, 2000;Zhang et al, 2002). Since serotonergic inputs have been shown to delay the maturation of inhibitory (GABAergic) influences on developing rhythmic circuits in the spinal cord (Branchereau et al, 2002;Allain et al, 2005), it is conceivable that the loss of 5HT neuron function results in premature switching to GABA-mediated inhibitory inputs to the respiratory central pattern generator, resulting in a longer period of depressed and unstable breathing in Pet-1 −/− mice.…”
Section: Serotonergic Function and Breathing Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Since catecholaminergic neurons in this region receive serotonergic synaptic input (Pickel et al, 1984), it is possible that the effects we have observed in 5HT neuron-deficient Pet-1 −/− mice are indirect and result from the loss of 5HT modulation of noradrenergic influences on central rhythm generation. In addition, a developmental switch from excitatory to inhibitory γ-aminobutyric acid (GABA)-mediated neurotransmission has been shown to occur in mouse preBötC neurons during the first postnatal week (Ritter and Zhang, 2000;Zhang et al, 2002). Since serotonergic inputs have been shown to delay the maturation of inhibitory (GABAergic) influences on developing rhythmic circuits in the spinal cord (Branchereau et al, 2002;Allain et al, 2005), it is conceivable that the loss of 5HT neuron function results in premature switching to GABA-mediated inhibitory inputs to the respiratory central pattern generator, resulting in a longer period of depressed and unstable breathing in Pet-1 −/− mice.…”
Section: Serotonergic Function and Breathing Stabilitymentioning
confidence: 99%
“…Several neurotransmitters including glutamate, substance P, GABA, and noradrenaline are known to influence respiratory network activity during these periods of respiratory maturation (Ritter and Zhang, 2000;Zhang et al, 2002;Hilaire et al, 2004;Thoby-Brisson et al, 2005;Hilaire, 2006;Zanella et al, 2006). In addition, a preponderance of physiological data indicate that respiratory drive is increased by exogenously applied serotonin (5HT) agonists or stimulation of endogenous 5HT release during the perinatal period, both in vivo and in vitro (for review, see Hilaire and Duron, 1999;Richerson, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…At early post-natal stages, GABA A receptormediated synaptic inhibition is functionally not present in many brain regions (Ballanyi and Grafe 1985;Cherubini et al 1991;Hara et al 1992;Gaiarsa et al 1995;Ritter and Zhang 2000). During the same period, GABA B receptors are not only functional (Cherubini et al 1991;Gaiarsa et al 1995), but they also seem to play a critical role in the synaptic modulation (Zhang et al 2002). Whereas GABA B receptors in adult animals exert both pre-synaptic and post-synaptic inhibitory effects (Misgeld et al 1995), during the early post-natal stage the inhibitory effects of GABA B receptor activation are either solely pre-synaptic, as shown in the rat hippocampus (Gaiarsa et al 1995), or post-synaptic, as shown in the brain stem of the mouse (Zhang et al 2002).…”
mentioning
confidence: 95%
“…Such information would be valuable for relating changes in cellular localisation and subcellular receptor trafficking of GABA B receptors to alterations in the functional role of GABA B receptors during post-natal development (Gaiarsa et al 1995;Zhang et al 2002). In the present study, specific antibodies were used to determine the cellular and subcellular localisations of GABA B R1 receptors in different brain regions of mice during post-natal development (P0-P66).…”
mentioning
confidence: 98%
See 1 more Smart Citation